Study of the therapeutic efficacy and safety of intralesional tranexamic acid (25 mg/ml) for the treatment of melasma in male patients: A single centered “before-after” observational study - Verma, Yog R.; Mehta, Karaninder S.; Chauhan, Pushpinder S.; Mahajan, Vikram K.; Chandel, Monika; Sharma, Hitender K.; Sharma, Anuj K.; Sharma, Reena K.; Chauhan, Amit (International Journal of Research in Dermatology, 2021)
Background: Melasma is a common and difficult to treat hypermelanosis of poorly understood etiopathogenesis with great tendency to relapse. Tranexamic acid (TA) has been used in various formulations for its treatment, but there is paucity of studies/data and no consensus on the optimum dosage of intradermal TA, especially among the male patients. To study the efficacy and safety of intralesional TA 25 mg/ml for the treatment of melasma in male patients. Methods: Total 58 males were enrolled for study from July 2019 to June 2020. TA in 25 mg/ml strength injection and about 0.05 ml was injected intradermally at 1 cm apart on the entire melasma lesion, not exceeding 50 mg per visit and repeated every 4 weekly for 12 weeks. The percentage reduction in MASI was the primary outcome measure. It was determined every 4th week till 12 weeks and finally at 24 weeks for recurrence. Results: Mean MASI decreased from baseline score of 8.42±5.63 to 6.71±4.65, 5.09±3.59 and 3.41±3.06 at the follow up week 4, 8 and 12 respectively with a significant decrease from 8th week onwards. Majority of the patients were satisfied with their improvement after treatment (67.2%) without any significant adverse effects. Conclusions: However, the TA was found to effective in all the three histopathological types of melasma but the dermal melasma was least responsive as well as earliest to relapse. We recommend monthly therapy at 25 mg/ml as more efficacious, time saving and cost effective to all the three types of melasma.